Bibliometrik literasi informasi pustakawan: Analisis tren penelitian di Pusat Perpustakaan dan Literasi Pertanian Bogor: Analysis of Research Trends at the Bogor Agricultural Library and Literacy Center - Regita Maharani Nyarji; Ninis Agustini Damayanti; Evi Nursanti Rukmana (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
Information literacy is an essential skill that librarians must possess to optimally support users' information needs. This study aims to analyze the trends and main themes in research on librarians' information literacy, with a focus on the Center for Library and Agricultural Literacy in Bogor. The method used is bibliometric analysis of relevant scientific publications to trace the frequency of keyword occurrences, the distribution of publications over time, and the contributions of institutions to the development of this topic. The results show that the terms "information literacy," "librarian," and "human" are the most frequently appearing keywords in these studies. These findings highlight the importance of strengthening the capacity of librarians, not only as collection managers but also as active facilitators of information literacy in the development of knowledge.